Rancangan Pembuatan Sarana Promosi di Taman Bacaan Masyarakat Suka Maju Sejahtera Padang - Putri, Windy Gustia; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
This research aims to design deskipsi the manufacture of means of promotion as a media campaign to promote children's Reading Society likes to move forward in prosperity to the general public, so the public can know the existence of the Grounds Advanced in prosperity the community Likes Reading. The draft making media campaign for children's Readings, Community Developed software Like corelDRAW X 4 and using fireworks CS3. CorelDRAW X 4 software selection and use of fireworks CS3 is the second such software is software that is used in the manufacture of media promotion with print media, although the fireworks are used in web designing, in the manufacture of means of promotion are also common. The Data collected through direct observation and interviews with owners and managers of children's Literature Community likes to move forward in prosperity. This type of research is a qualitative descriptive method. Keywords: software used; Park Community Library